Influence of Raman Pump Direction on the Performance of Serial Hybrid Fiber Amplifier in C+L-Band - Abdullah F.; Jamaludin M.Z.; Ali M.H.; Al-Mansoori M.H.; Abass A.K.; Al-Mashhadani T.F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fibers; Noise figure; Optical fiber communication; Photonics; Conventional techniques; Erbium doped fibers; Experimental validations; Hybrid fiber amplifier; Optical communication bands; Pump conversion; Raman pump; Recycling techniques; Fiber amplifiers